Final Results of the RHAPSODY Trial: A Multi‐Center, Phase 2 Trial Using a Continual Reassessment Method to Determine the Safety and Tolerability of 3K3A‐APC, A Recombinant Variant of Human Activated Protein C, in Combination with Tissue Plasminogen Activator, Mechanical Thrombectomy or both in Moderate to Severe Acute Ischemic Stroke. Issue 1 (7th January 2019) - Lyden, Patrick; Pryor, Kent E.; Coffey, Christopher S.; Cudkowicz, Merit; Conwit, Robin; Jadhav, Ashutosh; Sawyer, Robert N.; Claassen, Jan; Adeoye, Opeolu; Song, Shlee; Hannon, Peter; Rost, Natalia S.; et al.
Abstract : Objective: Agonism of protease‐activated receptor (PAR) 1 by activated protein C (APC) provides neuro‐ and vasculoprotection in experimental neuroinjury models. The pleiotropic PAR1 agonist, 3K3A‐APC, reduces neurological injury and promotes vascular integrity; 3K3A‐APC proved safe in human volunteers. We performed a randomized, controlled, blinded trial to determine the maximally tolerated dose (MTD) of 3K3A‐APC in ischemic stroke patients. Methods: The NeuroNEXT trial, RHAPSODY, used a novel continual reassessment method to determine the MTD using tiers of 120, 240, 360, and 540 μg/kg of 3K3A‐APC. After intravenous tissue plasminogen activator, intra‐arterial mechanical thrombectomy, or both, patients were randomized to 1 of the 4 doses or placebo. Vasculoprotection was assessed as microbleed and intracranial hemorrhage (ICH) rates. Results: Between January 2015 and July 2017, we treated 110 patients. Demographics resembled a typical stroke population. The MTD was the highest‐dose 3K3A‐APC tested, 540 μg/kg, with an estimated toxicity rate of 7%. There was no difference in prespecified ICH rates. In exploratory analyses, 3K3A‐APC reduced ICH rates compared to placebo from 86.5% to 67.4% in the combined treatment arms ( p = 0.046) and total hemorrhage volume from an average of 2.1 ± 5.8 ml in placebo to 0.8 ± 2.1 ml in the combined treatment arms ( p = 0.066). Interpretation: RHAPSODY is the first trial of a neuroprotectant for acute ischemic stroke in a trial design allowing thrombectomy, thrombolysis, or both. The MTD was 540 μg/kg for the PAR1 active cytoprotectant, 3K3A‐APC. A trend toward lower hemorrhage rate in an exploratory analysis requires confirmation. Clinical Trial Registration: Clinical Trial Registration‐URL:http://www.clinicaltrials.gov . Unique identifier: NCT02222714.ANN NEUROL 2019;85:125–136.